Preparation of biodiesel from RBD palm oil and WCO via alkaline transesterification process with the aid of NaOH as catalyst by batch process - Mohd Hafiz, Kamaludin @ Yusof (2009)
The fast depletion of fossil fuels, coupled with the increasing awareness of environmental issues, concern for increasing green house gas emissions and escalating petroleum prices, have led to concerted efforts in the search for renewable and environmentally friendly alternative energy sources. One of the alternative ways is by producing biodiesel. The purpose of this research is to examine the comparison on purity, yield and gas emission between RBD palm oil and waste cooking oil in the production of biodiesel by batch alkaline transesterification process. In the research, catalyst (NaOH) concentration of 0.25 wt% to 1.5 wt% was used. The temperature range used is fixed at 40°C and the time that be conducted is between 20 min to 60 min. The first parameter studied was catalyst concentration, where the highest value achieved was 0.75 wt% for RBD palm oil and 1.00wt% for WCO. 40 minutes was the highest reaction time obtained for RBD palm oil, while 50 minutes for WCO. The last parameter studied was the gas emission and the result showed that gas emission for biodiesel is better than gas emission produced by the fossil-based diesel. In comparison between RBD palm oil and WCO, WCO biodiesel produce more environmental friendly gases than RBD palm oil biodiesel.